Пентест дослідження як сервіс - Юхименко, В. І.; Федюшин, О. І. (ХНУРЕ, 2021)
The given work is dedicated to the introduction to penetration testing methodologies. One of the most reliable ways of maintaining information security is regular conducting of penetration testing. The main objective of penetration testing is to identify security weaknesses by simulation of real attacks. The methodology of pentest research as a service offered to clients of cloud services and local computers is considered. One of the possible architectures is offered
Keywords: тестування на проникнення; хмарні обчислення; PTaaS; локальна інфраструктура